A Rare Clinical Presentation of Lipoma- Palmar Lipomatosis - Khan, Mohd Shahbaaz; Maurya, Surendra; Kala, Sanjay (Journal of Diagnostics, 2017)
Introduction- Lipoma is the most common and most widely distributed tumor seen in the body. The most common clinical presentation is a gradually increasing, soft and non-tender mass. These tumours are very rare in hands and if they are present then they are of small size and usually one in number. Herewith we are presenting a case of Palmar Lipomatosis which had a large tumour and 4 small size tumour in same palm. Case report- Herewith we are reporting a case of a 40 years old female, presented with the complaints of multiple swellings in the right palm. She first noticed a small swelling on the thenar aspect of palm about 1½ years back; which was slowly, progressively increasing in size since then. Meanwhile patient also noticed some other swellings in the same palm. Incisions were given over thenar, hypothenar and at the bases of finger. All the tumors were removed en-masse. Biopsy report was fibrolipoma. Conclusion- Palmar lipoma is very rare tumour. Palm has very limited space for these tumours to grow but still these tumours can be found in palm. Very limited case reports about the lipoma of hand are present in literature. Here we presented a rare case of palmer lipomatosis which has multiple lipomatous swellings in same plam. They were removed successfully without any residual deformity.